THE POLICY ANALYSIS OF FDI IN THE FRAMEWORK OF LOCAL GOVERNMENT ECONOMY: A COMPARATIVE STUDY - Muhammad Iqbal Fadillah2, Idup Suhady1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
This paper discusses a comparative policy study of FDI that has been boosting local government economy in some selected countries. The output of this study is to provide empirical portrait about FDI policy that can be applied in Indonesia. This study was conducted through 2 (two) approaches: first, a comparative policy study on FDI in Singapore, Japan, South Korea, Malaysia, Vietnam, China; and second, a study on FDI policy in some regions in Indonesia. Finally, this paper proposespolicy recommendations to the regions for improving their foreign direct investments in order to foster their economic development.